Self-directed learners' perceptions and experiences of learning computer science through MIT open courseware. (2nd October 2022) - Zhu, Meina; Kadirova, Dilnoza
ABSTRACT: Given the rapid rise of open educational resources (OER) for informal learning pursuits impacting countless millions of people each day around the world, this study investigated the impact of the initiative that spearheaded this movement; namely, Massachusetts Institute of Technology (MIT) open courseware (OCW). More specifically, it explored self-directed learners' perceptions of the impact of the MIT OCW, their social presences and cognitive presences while learning through MIT OCW online instructional videos. The data source of this study was learner comments regarding 23 instructional videos found in YouTube. Thematic analysis and computer-mediated discourse analysis (CMDA) were used for data analysis. The results indicated that the impact of the MIT OCW served as the first step for career development and important educational decisions of myriad learners that served to benefit MIT programmes with future applicants. In addition, YouTube comments of the self-directed learners reflected a relatively lower social presence and higher cognitive presence compared to general social media. Meanwhile, self-directed learners encountered challenges such as technology issues, non-engaging teaching methods, and social learning needs. Perhaps the future OER and OCW development will, in fact, be designed for a more interactive and engaging experience for the self-directed learners of this world.